Refinement of estimates of mortality risk using the Radiologic Severity Index in hematologic malignancy patients with respiratory syncytial virus infection. Issue 4 (28th May 2019) - Sheshadri, Ajay; Karimipour, Mahtab; Vakil, Erik; Bashoura, Lara; Godoy, Myrna; Arain, Muhammad H.; Evans, Scott E.; Dickey, Burton F.; Ost, David E.; Chemaly, Roy F.; Faiz, Saadia A.
Abstract: Background: Immunocompromised hematologic malignancy (HM) patients experience high mortality after respiratory syncytial virus (RSV) lower respiratory tract infection (LRTI). We measured radiologic severity to determine whether it could improve the performance of 60‐day mortality models based only upon immunodeficiency severity. Methods: We studied 155 HM patients, including 84 hematopoietic cell transplant recipients, who developed RSV LRTI from 2001 to 2013. We measured immunodeficiency using lymphopenia (lymphocyte count <200 cells/mm 3 ), Immunodeficiency Severity Index (ISI), and Severe Immunodeficiency (SID) criteria. Radiologic severity was measured by the Radiologic Severity Index (RSI, range 0‐72) at time of LRTI (baseline‐RSI) and peak severity (peak‐RSI). Delta‐RSI was defined as the difference between baseline‐RSI and peak‐RSI. We used logistic regression models to measure the association of immunodeficiency and RSI with 60‐day all‐cause mortality, and measured model discrimination using areas under the receiver‐operating characteristics curves, calibration using Brier scores, and explained variance using pseudo‐ R 2 values. Results: Forty‐one patients died within 60 days of RSV LRTI. Severe immunodeficiency was associated with higher mortality. Peak‐RSI (odds ratio [OR] 1.06/point, 95% confidence interval [CI] 1.04‐1.08), and delta‐RSI (OR 1.07/point, 95% CI 1.05‐1.10) were associated with 60‐day mortality after RSV LRTI, but not baseline‐RSI. Addition of peak‐RSI or delta‐RSI to baseline immunodeficiency improved the discrimination, calibration, and explained variance ( P  < 0.001) of 60‐day mortality models. Conclusions: Although baseline immunodeficiency in HM patients helps predict 60‐day mortality after RSV LRTI, mortality risk estimates can be further refined by also measuring LRTI progression using RSI. RSI is well‐suited as a marker of LRTI severity in RSV infection.